Persepsi Mahasiswa terhadap Peer-Assisted Learning dalam Proses Pembelajaran di Fakultas Kedokteran Universitas Lampung: Sebuah Studi Kualitatif - Muhammad Rifath Akbar; Dwita Oktaria; Khairun Nisa; Merry Indah Sari (Majority, 2020)
Peer-assisted learning (PAL) is one of the teaching methods used in the Faculty of Medicine Lampung University. PAL is learning undertaken by fellow students, and it does not involve professional lecturer in the process. This study aims to describe in depth the students' perceptions of PAL in the learning process at the Faculty of Medicine, Lampung University. This study used a qualitative research design with a phenomenological approach and for participant recruitment technique in this study used maximum sampling variation. Main participants in this study were students of the class of 2016 and 2015, consisting of 24 people who were men and women, peer tutors, and peer tutees. The main data were retrieve5d through focus group discussions held 3 times, while a triangulation of data researchers used in-depth interviews with lecturers who conduct PAL, and PAL activity observations. There were many perceptions of students regarding definition and benefits of PAL, and factors that affected PAL which included supporting factors, such as good communication of peer tutors and materials, provided by peer tutors, which corresponded to the purpose of learning. Factors which could interfere the implementation of PAL included realization, peer tutor, and peer tutees readiness, There was also students perception regarding hope for PAL implementation, for examples, conducting PAL in CSL, usage of technology, and evaluation in the implementation. Perception of students on PAL at Faculty of Medicine Lampung University showed that both peer tutor and peer tutees influence one another in the implementation.